2018
DOI: 10.1021/acsami.8b01513
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Proton Conductivity and Thermal Stability in Nafion Membranes Induced by Incorporation of Sulfonated Carbon Nanotubes

Abstract: Proton exchange membrane fuel cell (PEMFC) is one of the most promising green power sources, in which perfluorinated sulfonic acid ionomer-based membranes (e.g., Nafion) are widely used. However, the widespread application of PEMFCs is greatly limited by the sharp degradation in electrochemical properties of the proton exchange membranes under high temperature and low humidity conditions. In this work, the high-performance sulfonated carbon nanotubes/Nafion composite membranes (Su-CNTs/Nafion) for the PEMFCs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(85 citation statements)
references
References 62 publications
3
74
0
Order By: Relevance
“…[39][40][41] By decreasing the humidity rate the differences among the devices became significant and in accordance to the following trend: ECD-A < SPED << ECD-B. [39][40][41] By decreasing the humidity rate the differences among the devices became significant and in accordance to the following trend: ECD-A < SPED << ECD-B.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 72%
“…[39][40][41] By decreasing the humidity rate the differences among the devices became significant and in accordance to the following trend: ECD-A < SPED << ECD-B. [39][40][41] By decreasing the humidity rate the differences among the devices became significant and in accordance to the following trend: ECD-A < SPED << ECD-B.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 72%
“…Some authors also reported a decrease in the membrane permeability to methanol as well as its crossover in direct methanol fuel cells with CNTs introduction [ 237 ]. The use of carbon nanotubes with a sulfonated surface for this purpose is especially effective, since they can increase the proton conductivity of membranes due to additional charge carrier introduction [ 239 , 240 , 241 , 242 ]. Moreover, the negatively charged surface of sulfonated CNTs creates an additional double electric layer around them and increases the membrane selectivity.…”
Section: Hybrid Membranesmentioning
confidence: 99%
“…Generally, both of the surface charge and the tunnels in the membrane would influence the permeation of ions. [13,14] For GO based membrane, the polar groups definitely endow the charges on membrane surface, so the Donnan repulsive interaction should be considered during the separation process. [15,16] In addition, the interlayer spacing between the GO platelets is not fixed in solution.…”
Section: Introductionmentioning
confidence: 99%